2011
DOI: 10.1002/jmri.23535
|View full text |Cite
|
Sign up to set email alerts
|

Single breathhold noncontrast thoracic MRA using highly accelerated parallel imaging with a 32‐element coil array

Abstract: OBJECTIVE To evaluate the feasibility of performing single breath-hold 3D thoracic non-contrast magnetic resonance angiography (NC-MRA) using highly-accelerated parallel imaging. MATERIALS AND METHODS We developed a single breath-hold NC MRA pulse sequence using balanced steady state free precession (SSFP) readout and highly-accelerated parallel imaging. In 17 subjects, highly-accelerated non-contrast MRA was compared against electrocardiogram (ECG)-triggered contrast-enhanced MRA. Anonymized images were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, ECG-gated CE-MRA does not provide the same high image quality of ECG-and navigator gated non-CE-MRA techniques such as 3D SSFP for the aortic root [11,30]. Additionally, ECG-gating proves to be challenging and leads to prolonged scan time potentially resulting in suboptimal contrast phase, especially in bradycardic patients; therefore, non-ECG-gated CE-MRA is still the most widely used technique in clinical routine [38].…”
Section: Limitationsmentioning
confidence: 99%
“…However, ECG-gated CE-MRA does not provide the same high image quality of ECG-and navigator gated non-CE-MRA techniques such as 3D SSFP for the aortic root [11,30]. Additionally, ECG-gating proves to be challenging and leads to prolonged scan time potentially resulting in suboptimal contrast phase, especially in bradycardic patients; therefore, non-ECG-gated CE-MRA is still the most widely used technique in clinical routine [38].…”
Section: Limitationsmentioning
confidence: 99%
“…Most previous studies assessed the image quality of the thoracic aorta with ECG-triggered SSFP-MRA versus non-ECG-triggered CE-MRA using visual classification criteria [ 18 , 19 , 28 , 29 , 31 , 33 ], whereas one lacked these criteria [ 15 ] and another two studies used a semi-automatic approach [ 24 , 30 ]. Despite the variation of methods, all studies reported improved image quality with SSFP-MRA for the aortic root [ 15 , 19 , 28 31 , 33 , 34 ]. Some studies also reported increased image quality of the mid-ascending aorta [ 19 , 24 , 29 , 30 , 34 ] and mid-descending aorta [ 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches used lower acceleration factor of 2. Although parallel imaging has been used with higher rate for breath-hold non-contrast thoracic MRA [ 47 , 48 ], its feasibility for free breathing CE-PV MRA has not been shown yet. Furthermore, due to noise penalty induced by the g-factor maps, parallel imaging has been shown to result in higher noise level than compressed sensing [ 41 ].…”
Section: Discussionmentioning
confidence: 99%